If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 4 = 11 + -1t Reorder the terms: 4 + 2t = 11 + -1t Solving 4 + 2t = 11 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. 4 + 2t + t = 11 + -1t + t Combine like terms: 2t + t = 3t 4 + 3t = 11 + -1t + t Combine like terms: -1t + t = 0 4 + 3t = 11 + 0 4 + 3t = 11 Add '-4' to each side of the equation. 4 + -4 + 3t = 11 + -4 Combine like terms: 4 + -4 = 0 0 + 3t = 11 + -4 3t = 11 + -4 Combine like terms: 11 + -4 = 7 3t = 7 Divide each side by '3'. t = 2.333333333 Simplifying t = 2.333333333
| 162=18(2a+14) | | 15=-9x+50 | | x^5-9x^4+34x^3-66x^2+65x-25=0 | | K+1/6=4K+1/6 | | 2x-1+3=x-3x-1 | | 6x+1=3(2x+1)-x+4 | | 15r^2+8-16= | | 4x^2+12-40= | | 4-6x=-5 | | 2m^2+15m+14= | | 1.5(x+8)=3.9+.6x | | -18-(-5)= | | (3x-5y)*3= | | x+3x-50m=0 | | x^2+17xy+72y^2= | | 6n-12=-12 | | 2.96= | | 3x+11=30 | | f=lry | | 12x+20=10x-35 | | 10/23w | | 2b-4x=a+x | | (0.06(y-6)+0.16y)=0.02y-0.03(40) | | 9x+28=50 | | 2t^5-16t^4+30t^3= | | (-1/6)*(x-18)+(1/3)*(x+3)=x+19 | | (m^2n)^7/m^7n^2 | | 70b=50 | | -(1/6)(x-12)+(1-3)(x+3)=x-2 | | 5t^5-30t^4+40t^3= | | graphx-y=4 | | x^2+2x=128 |